Application of raman spectroscopy for characterization of natural stone sludge waste. (2020) - Gupta, Vivek; Pathak, Devesh K.; Kumar, Rajesh; Chaudhary, Sandeep
Abstract: The proper management of a vast amount of natural stone waste generated from various stone processing industries of economic and environmental importance. The current study characterizes four different types of sludge stone waste to understand their potential as building material. The different types of stone wastes were characterized using Raman spectroscopy and identified through different bonds present in the material. In the end, conclusions were drawn to recommend the potential application area for different types of natural stone wastes.